2017
DOI: 10.1111/bdi.12516
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and hippocampus volumes are differently affected by childhood trauma in patients with bipolar disorders and healthy controls

Abstract: The results suggest that childhood trauma may have a different effect in health and disease on volumes of gray matter in the amygdala and hippocampus, which are brain areas specifically involved in response to stress and emotion processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 59 publications
3
32
0
4
Order By: Relevance
“…64 For instance, the effect of childhood trauma on subcortical volumes in BD patients produces specific changes in grey matter volumes of the amygdala, hippocampus, and pre-frontal regions, which are key areas for emotional regulation and are involved in suicide attempts. 12,30,65 In individuals who have experienced CM, BD emerges earlier, 24 with greater severity, 38 greater comorbidity, 66 more suicidal behavior, 40,53 and treatment resistance. 5,40 Nevertheless, these negative outcomes are likely not unique to BD, since recent investigations have shown that CM is associated with an increased risk of SB in patients with schizophrenia, 67 alcoholism, 68 personality disorders, 69 and substance abuse, 70 as well in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…64 For instance, the effect of childhood trauma on subcortical volumes in BD patients produces specific changes in grey matter volumes of the amygdala, hippocampus, and pre-frontal regions, which are key areas for emotional regulation and are involved in suicide attempts. 12,30,65 In individuals who have experienced CM, BD emerges earlier, 24 with greater severity, 38 greater comorbidity, 66 more suicidal behavior, 40,53 and treatment resistance. 5,40 Nevertheless, these negative outcomes are likely not unique to BD, since recent investigations have shown that CM is associated with an increased risk of SB in patients with schizophrenia, 67 alcoholism, 68 personality disorders, 69 and substance abuse, 70 as well in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala receives conditioned stimuli from sensory inputs, meditates defensive reactions (such as freezing, autonomic nervous system activity and hormonal release) by modulating hypothalamic nuclei activity and manages goal-directed actions by modulating ventral striatum activity ( LeDoux, 2000 , 2012 ; Davis et al, 2010 ). Alterations in emotion may lead to different mental illness and have been associated with diseases such as bipolar disorder ( LeDoux, 2000 ; Saxena et al, 2012 ; Townsend et al, 2013 ; Janiri et al, 2017 ) and ADHD ( Humphreys et al, 2016 ). In rats, AC projecting areas are involved mostly in olfactory, anxiety and fear behavior ( Amaral, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal connectivity of limbic and several neocortical areas that are contra laterally connected through the anterior commissure (AC) have been found in some of these diseases. Altered emotion, controlled by limbic areas, has been associated with bipolar disorder ( LeDoux, 2000 ; Saxena et al, 2012 ; Townsend et al, 2013 ; Janiri et al, 2017 ) and ADHD ( Humphreys et al, 2016 ). Recently, magnetic resonance imaging (MRI), has been used to observe abnormal development of interhemispheric connections in children born to women treated for hypothyroidism at different periods of pregnancy, demonstrating the contribution of maternal thyroid hormone to this process ( Samadi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study found the effects of childhood maltreatment on white matter structural integrity was specific to individuals with bipolar disorder-decreased structural integrity was not observed in healthy comparison individuals with a history of childhood maltreatment compared to healthy individuals without maltreatment [214]. In light of this finding, and recently published data from other groups [216][217][218], it is possible some consequences following childhood maltreatment may be more robust or distinct in some individuals-or that perhaps individuals with genetic predisposition for mood disorders may be more vulnerable to the detrimental effects of childhood maltreatment. Altered amygdala and hippocampal volumes are suggested to be differentially modulated following childhood maltreatment in patients with bipolar disorder compared to a healthy comparison group [216], although interactions with history of treatment, e.g.…”
Section: Childhood Maltreatment and Associated Alterations In Neural mentioning
confidence: 92%